Development of software for controlling the movement of jib crane mechanisms - Romasevych, Y.; Loveikin, V. (Energy and Automation, 2025)
The article provides an overview of software products from leading developers of software for the operation of cranes. The statement and solution of the problems of optimal control of the movement of the mechanisms of load hoisting and slewing the jib crane in the acceleration and braking modes are presented. Calculations were carried out for three quadratic integral quality criteria, which reflected the driving factors and their higher derivatives in time up to the second inclusive. The laws of change of the driving elements (angular velocities of the drives of the mechanisms) were obtained, which ensure the implementation of optimal control. The software "Optimal control of the movement of jib crane mechanisms" was developed, which allows using frequency-controlled drives of both mechanisms to implement optimal control in practice. A description of the communication settings between frequency converters and a computer with the developed software via a serial communication port is presented. The sequence of actions of the user of the software product is shown in order to calculate the optimal laws of motion, their visualization and transmission of control commands to frequency converters to perform tasks of optimal control of the movement of mechanisms.Key words: hoisting crane, software, optimal control, development